Designing 3D interconnected continuous nanoporous Co/CoO core–shell nanostructure electrodes for a high-performance pseudocapacitor. (18th January 2017) - Qing, Chen; Zhou, Qin; Qu, Gan; Chen, Xinqi; Wang, Hai; Sun, Daming; Wang, Bixiao; Xu, Lifeng; Tang, Yiwen
Abstract: A high-performance supercapacitor electrode is designed and fabricated with the 3D interconnected continuous nanoporous Co/CoO core–shell hybrid nanostructure grown on nickel foam. The Co/CoO core–shell hybrid nanostructures are obtained via a hydrothermal method, followed by high-temperature annealing in hydrogen atmosphere, and finally placed in air at 50 °C for 1 h. The Co/CoO core–shell nanostructure assembled by a conductive metal–core and a CoO shell, brings low resistance, high specific capacitance of 5.632 F cm −2 and good capability stability (81.5% capacitance retention after 6000 cycles). An asymmetric supercapacitor device built by the Co/CoO (positive electrode) and activated carbon (negative electrode) can deliver a working voltage of 1.7 V and display a high energy density of 0.002 67 Wh cm −2 at a power density of 0.001 62 W cm −2, which is far superior to that of a supercapacitor at a similar power density.